The Natural Course of Eosinophilic Esophagitis and Long‐Term Consequences of Undiagnosed Disease in a Large Cohort. (June 2018) - Warners, Marijn J.; Oude Nijhuis, Renske A. B.; de Wijkerslooth, Laetitia R. H.; Smout, Andreas J. P. M.; Bredenoord, Albert J.
Abstract : BACKGROUND: Eosinophilic esophagitis (EoE) is a chronic esophageal inflammation that may lead to stricture formation. This narrowing can cause major complications including food impactions. Despite increasing interest in EoE accurate data on its natural course is scarce. Therefore, we aimed to investigate the natural course of EoE and to evaluate the association between undiagnosed disease and the occurrence of complications over two decades in a large cohort. METHODS: We retrospectively analyzed charts of patients diagnosed with EoE between 1996 and 2015, collected from 15 hospitals throughout the Netherlands. Histologic, clinical, and endoscopic characteristics were identified and stratified by age and diagnostic delay. RESULTS: We included 721 patients (524 males, 117 children (≤18 years)). Dysphagia and food impactions were more common in adults whereas children more often presented with vomiting and abdominal pain (all p < 0.001). The prevalence of fibrotic endoscopic features was higher in adults (76%) than in children (39%) ( p < 0.001). As time with undiagnosed disease progressed the percentage of patients with strictures and food impactions increased from 19% and 24% (diagnostic delay ≤ 2 years) to 52% and 57% (diagnostic delay ≥ 21 years) ( p < 0.001), respectively. In a multivariate logistic regression model, diagnostic delay (odds ratio (OR) = 1.09; 95% confidence interval (CI) = 1.05–1.13) and male gender (OR = 2.69, 95% CI = 1.61–4.50) were the major risk factors for stricture presence. CONCLUSION: During the natural course of EoE, progression from an inflammatory to a fibrostenotic phenotype occurs. With each additional year of undiagnosed EoE the risk of stricture presence increases with 9%. SUPPLEMENTARY MATERIAL accompanies this paper at https://doi.org/10.1038/s41395–018–0052–5